Conceptualisation of love in Russian, Macedonian and Slovenian - Nikolovski, Gjoko; Mirchevska-Bosheva, Biljana (Slavia Centralis, 2022)
The focus of the paper is the conceptualisation of love in Russian, Macedonian and Slovene through the prism of the cognitive theory of metaphor. To this end, material is being analysed that signifies deep and intimate emotion and strong affection for the other person. The starting point is the Russian material, for which we are looking for parallels in Macedonian and Slovenian. The collected material is arranged according to 15 metaphors representing different aspects of this complex phenomenon, in order to identify the differences and similarities in the conceptualisation of love in all three languages. The initial hypothesis of the article is that such a conceptualisation of love can be realised with the help of phraseological and non-phraseological material, which gives a broader view of the definition of love as an emotional phenomenon in Russian, Macedonian and Slovenian.